Molecular cloning and characterization of O-methyltransferase from mango fruit (mangifera indica cv. alphonso) - Chidley, Hemangi G.; Oak, Pranjali S.; Deshpande, Ashish B.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Molecular Biotechnology, 2016)
Flavour of ripe Alphonso mango is invariably dominated by the de novo appearance of lactones and furanones during ripening. Of these, furanones comprising furaneol (4-hydroxy-2,5-dimethyl-3(2H)-furanone) and mesifuran (2,5-dimethyl-4-methoxy-3(2H)-furanone) are of particular importance due to their sweet, fruity caramel-like flavour characters and low odour detection thresholds. We isolated a 1056 bp complete open reading frame of a cDNA encoding S-adenosyl-l-methionine-dependent O-methyltransferase from Alphonso mango. The recombinantly expressed enzyme, MiOMTS showed substrate specificity towards furaneol and protocatechuic aldehyde synthesizing mesifuran and vanillin, respectively, in an in vitro assay reaction. A semi-quantitative PCR analysis showed fruit-specific expression of MiOMTS transcripts. Quantitative real-time PCR displayed ripening-related expression pattern of MiOMTS in both pulp and skin of Alphonso mango. Also, early and significantly enhanced accumulation of its transcripts was detected in pulp and skin of ethylene-treated fruits. Ripening-related and fruit-specific expression profile of MiOMTS and substrate specificity towards furaneol is a suggestive of its involvement in the synthesis of mesifuran in Alphonso mango. Moreover, a significant trigger in the expression of MiOMTS transcripts in ethylene-treated fruits point towards the transcriptional regulation of mesifuran biosynthesis by ethylene.
Keywords: Ethylene; expression; Flavour; Mango; Mesifuran; Ripening